2015
DOI: 10.1016/j.toxrep.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the toxic effect of potential human carcinogen Microcystin-LR on testis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 47 publications
(71 reference statements)
0
64
0
Order By: Relevance
“…In addition, the study of Chen and Xie [40] has raised questions and great concerns about the probable reproductive toxicity of MCs. Recent studies have verified that MCs accumulate in testis [32,50,51] and ovary [44,52], and exert toxic effects on the reproductive system [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study of Chen and Xie [40] has raised questions and great concerns about the probable reproductive toxicity of MCs. Recent studies have verified that MCs accumulate in testis [32,50,51] and ovary [44,52], and exert toxic effects on the reproductive system [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…microcystin-LR (MC-LR) is the most toxic microcystin amongst approximately 100 congeners of the known microcystins [3]. The heptapeptide is reported to be hepatotoxic [4] and a potential human carcinogen [5]. Therefore, a guideline of 1 µg·L −1 has been set for this toxin by the World Health Organization (WHO) for drinking water quality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the toxicity to the gonad, induced by MC‐LR, have found that MC‐LR can accumulate in the reproductive systems of mice, rats, amphibians, and fishes . Furthermore, previous studies have shown that MC‐LR can increase reactive oxygen species (ROS) and decrease the expression of more than 100 kinds of microRNAs in spermatogonia .…”
Section: Introductionmentioning
confidence: 99%